Upaya Guru Pendidikan Agama Islam dalam Meningkatkan Prestasi Belajar Siswa - Daulay, Abdul Sattar (Darul Ilmi: Jurnal Ilmu Kependidikan dan Keislaman, 2022)
This study aims to determine the efforts made by teachers to improve learning achievement in Islamic Religious Education at SMP Negeri 5 Panyabungan, Panyabungan District, Mandailing Natal Regency, and to find out what are the obstacles in improving student achievement at SMP Negeri 5 Panyabungan, Panyabungan District, Mandailing Natal Regency. The research method used in this research is to use a qualitative approach with a descriptive method that is to describe the phenomena or events that occur in the field as they are. The data collection instrument used consisted of observation and interviews and. The results of this study are the teacher's efforts to improve learning achievement in Islamic Religious Education, namely by providing student learning guidance, making varied methods of teaching, optimizing the use of learning media and providing motivation for students to study more actively in Islamic Religious Education lessons, and giving gifts or praise to outstanding students.